STRATEGI GURU DALAM MENGEMBANGKAN KEMAMPUAN KOMUNIKASI DAN MOTORIK ANAK BERKEBUTUHAN KHUSUS - Hartanti Pungkas Baya; Nia Kurniasih; Denti Ariyanti; Nining Yuningsih; Anty Noeryanti; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the strategies used by teachers in developing communication and motor skills for children with special needs (CSN) in special schools. Communication and motor skills are fundamental to the independence and social interaction of CSN, but their development requires an adaptive approach according to the type and level of children's barriers. The method used is a literature study with a qualitative descriptive approach, analyzing various research results and scientific literature related to learning strategies for CSN. The results show that teacher strategies include: (1) the use of total communication (verbal, sign, and pictures) based on Augmentative and Alternative Communication (AAC), (2) the application of play therapy and sensorimotor activities to develop gross and fine motor skills, and (3) an individual approach through Individual Learning Programs (PPI). The success of the strategy is largely determined by teacher competence, collaboration with therapists and parents, and the availability of adequate assistive devices. This study recommends the need for continuous training for teachers on assistive technology and evidence-based early intervention approaches.